Rheumatic diseases and musculoskeletal pain - Rahman, Anisur (Henry Stewart Talks, 2018)
Current status of and challenges in the research into therapeutic interventions for antiphospholipid syndrome (APS), The hurdles pharmaceutical companies are facing on their way to developing APS treatments, Dealing with increased cardiovascular risks in patients with rheumatic autoimmune diseases, Challenges in lupus clinical trials, Current challenges in developing chronic musculoskeletal pain treatments